2014
DOI: 10.1016/j.aucc.2013.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a track and trigger system is associated with increased paediatric intensive care outreach utilisation and a trend towards improved patient outcomes in a tertiary children's hospital

Abstract: Patients requiring ECMO have acquired haemostatic disorders due to a vast interplay of factors including drugs, disease and device. In this heterogenous population it is impossible to define the isolated and combined effects of critical illness and ECMO on haemostasis.This study aimed to characterise changes in haemostasis attributable to ECMO in an in vivo ovine model using ROTEM ® and Multiplate ® analysis. In our validated model, 10 healthy sheep and 10 sheep with smoke-induced acute lung injury (S-ALI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…One uncontrolled before-after study in a community hospital (without RRT/MET) found significant postintervention reductions in rates of urgent calls to the in-house paediatrician (RR=0.23, 95% CI 0.11 to 0.46) and respiratory therapist70 (RR=0.36, 95% CI 0.13 to 0.95). Two uncontrolled before-after studies (with RRT/MET) found increases in rates of RRT calls72 (RR=1.59, 95% CI 0.33 to 1.90) and outreach team calls66 (RR=1.92, 95% CI 1.79 to 2.07). One study found no change in rates of RRT calls 71…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One uncontrolled before-after study in a community hospital (without RRT/MET) found significant postintervention reductions in rates of urgent calls to the in-house paediatrician (RR=0.23, 95% CI 0.11 to 0.46) and respiratory therapist70 (RR=0.36, 95% CI 0.13 to 0.95). Two uncontrolled before-after studies (with RRT/MET) found increases in rates of RRT calls72 (RR=1.59, 95% CI 0.33 to 1.90) and outreach team calls66 (RR=1.92, 95% CI 1.79 to 2.07). One study found no change in rates of RRT calls 71…”
Section: Resultsmentioning
confidence: 99%
“…There was also limited evidence for early warning systems reducing PICU transfers or calls for urgent review. Again, a small number of uncontrolled before-after studies reported significant reductions postintervention,15 17 63 but several other studies reported significant increases in transfers or calls for review66 72 or no postintervention changes. We did find moderate evidence across four studies—including a controlled before-after study, a multicentre interrupted time series study and a multicentre cluster randomised trial—for early warning system interventions reducing rates of early critical interventions in children transferred to PICU 64 65 68 69.…”
Section: Discussionmentioning
confidence: 99%
“…105 Two uncontrolled before-and-after studies (with RRTs/METs) found increases in the rates of RRT calls (RR 1.59, 95% CI 1.33 to 1.90) 107 and outreach team calls (RR 1.92, 95% CI 1.79 to 2.07). 101 One study found no change in the rate of RRT calls. 106 Paediatric intensive care unit transfers…”
Section: Type Of Early Warning System Interventionsmentioning
confidence: 99%
“…Seventeen interventions involved the introduction of a new PTTT, 38,[46][47][48][49]84,[96][97][98][99][100][101][102][103][104][105][106][107] one intervention introduced a mandatory triggering element to an existing PTTT 106 and one study reported a large, multicentre analysis of MET introduction with no details on PTTT use. 108 Twelve interventions included the introduction of a new MET or RRT, 38,[46][47][48][49]84,[96][97][98][99][100]104 and four further interventions 87,89,100,106 introduced a new PTTT in a hospital with an existing MET or RRT.…”
Section: Type Of Early Warning System Interventionsmentioning
confidence: 99%
See 1 more Smart Citation